2016
DOI: 10.3389/fmicb.2016.01796
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Alpha-Momorcharin and Jasmonic Acid in Modulating the Response of Momordica charantia to Cucumber Mosaic Virus

Abstract: Alpha-momorcharin (α-MMC) is a type-I ribosome inactivating protein with a molecular weight of 29 kDa that is found in Momordica charantia, and has been shown to be effective against a broad range of human viruses as well as having anti-tumor activities. However, the role of endogenous α-MMC under viral infection and the mechanism of the anti-viral activities of α-MMC in plants are still unknown. To study the effect of α-MMC on plant viral defense and how α-MMC increases plant resistance to virus, the M. chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 47 publications
3
19
0
6
Order By: Relevance
“…The candidate gene encodes a ribosome-inactivating protein related to the defense response. The results are consistent with those of Yang et al (2016), who reported a positive correlation between the level of ribosomeinactivating protein (RIP) and resistance to cucumber mosaic virus in Momordica charantia. RIPs can induce apoptosis in a wide variety of cells (Narayanan et al, 2005), which plays a role in the regulation of cell death induced by the herbicide.…”
Section: Discussionsupporting
confidence: 91%
“…The candidate gene encodes a ribosome-inactivating protein related to the defense response. The results are consistent with those of Yang et al (2016), who reported a positive correlation between the level of ribosomeinactivating protein (RIP) and resistance to cucumber mosaic virus in Momordica charantia. RIPs can induce apoptosis in a wide variety of cells (Narayanan et al, 2005), which plays a role in the regulation of cell death induced by the herbicide.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, application of α-MMC can increase the expression of NPR1, PR1 , and PR2 in tobacco plants, which strongly indicates that the plant systemic resistance can be activated by α-MMC against multiple viruses ( Zhu et al, 2013 ). Furthermore, application of α-MMC in M. charantia led to a significant increase of JA indicated that the anti-viral activities of α-MMC in M. charantia may be accomplished through the JA related signaling pathway ( Yang et al, 2016 ). Therefore, it may be a candidate for the development of virus resistant crop plants, for instance cotton, tobacco, rice, tea, and clover.…”
Section: Introductionmentioning
confidence: 99%
“…‘Lane late’ navel orange, late mature Citrus clementina , WT and MT fruit were dipped in 10 μM MeJA for 10 min and distilled water was used as a control as described by Droby et al 25 . For the JA inhibitor treatment, above-mentioned fruit were dipped in 100 μM PG (Sigma-Aldrich), 100 μM IBU (Sigma-Aldrich) and 1.5 mM DIECA (Sigma-Aldrich) for 30 min, and distilled water was used as control 20 22 . The inoculation and incubation followed the same procedures described above.…”
Section: Methodsmentioning
confidence: 99%
“…The natural variation in allene oxide synthase2 ( AOS2 ) in potato affects the level of jasmonate and influences pathogen resistance in Arabidopsis 3 . The inhibitors of JA synthesis pathway are diethyldithiocarbamic acid (DIECA, an AOS inhibitor), ibuprofen (IBU, a lipoxygenase inhibitor) and n-propyl gallate (PG, a less specific inhibitor of both LOX and allene oxide cyclase (AOC)) 20 22 . The orthologs of Arabidopsis 13-LOXs , AOC , and AOS are actively present in citrus 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation